Effects of structural microdomains on the vortex correlation length in a-axis oriented EuBa2Cu3O7 thin films - Gonzalez, E.M. (2006)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina